Conductance switching in an organic material: from bulk to monolayer - Rath, Arup Kumar; Pal, Amlan J. (Langmuir, 2007)
Fluorescein sodium, which does not exhibit electrical bistability in thin films, can be switched to a high conducting state by the introduction of carbon nanotubes as channels for carrier transport. Thin films based on fluorescein sodium/carbon nanotubes display memory switching phenomenon among a low conducting state and several high conducting states. Read-only and random-access memory applications between the states resulted in multilevel memory in these systems. Results in thin films and in a monolayer (deposited via layer-by-layer assembly) show that instead of different molecular conformers, multilevel conducting states arise from the different density of high conducting fluorescein molecules.